Virtualpolitik : an electronic history of government media-making in a time of war, scandal, disaster, miscommunication, and mistakes - Losh, Elizabeth M. (Elizabeth Mathews) (MIT Press, 2009)
Government media making, from official websites to whistleblowers' e-mail, and its sometimes unintended consequences.